1987
DOI: 10.1111/j.1943-278x.1987.tb00057.x
|View full text |Cite
|
Sign up to set email alerts
|

A Drop in Suicides around Major National Holidays

Abstract: To study the fluctuation of suicides around the holidays, we examined 188,047 U.S. suicides from 1973 to 1979. Correcting for the effects of extraneous variables, such as seasons and days of the week, we found that suicides dropped by an annual average of -102.5 in the period surrounding the holidays. One set of holidays (Memorial Day, Thanksgiving, and Christmas) was associated with an unusually low risk of suicide before, during, and after the holiday. Another set of holidays (New Year's Day, July 4th, and L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
1

Year Published

1991
1991
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 17 publications
3
42
1
Order By: Relevance
“…The major Jewish holidays (Rosh Hashana, Yom Kippur, Succot) occur, in effect, during the months of September-October, a period which coincides with the trough observed by Schreiber et al [66] in their time series. A major effect of national holidays on suicidal behaviour had previously also been reported in the USA: Phillips and Wills [67] found a drop in the suicide rate in the few days before as well as during all holidays.…”
Section: Discussionmentioning
confidence: 98%
“…The major Jewish holidays (Rosh Hashana, Yom Kippur, Succot) occur, in effect, during the months of September-October, a period which coincides with the trough observed by Schreiber et al [66] in their time series. A major effect of national holidays on suicidal behaviour had previously also been reported in the USA: Phillips and Wills [67] found a drop in the suicide rate in the few days before as well as during all holidays.…”
Section: Discussionmentioning
confidence: 98%
“…Holidays are said to lower suicide risk through promoting increased interaction among friends and family. Phillips and Wills (1987) present some data, in passing, on nonwhites. They re port that blacks experienced a drop of 10.16 suicides during holiday periods compared with a drop of 55.52 for whites.…”
Section: Day Of the Weekmentioning
confidence: 98%
“…Third, the present study employs national data. Most of the previous research on temporal effects has been based on local samples, which raises questions about the generalizability of the findings (see reviews in Phillips and Wills 1987;Cheatwood 1988;Gabennesch 1988). …”
mentioning
confidence: 97%
See 1 more Smart Citation
“…For example, holidays suppress suicides. These effects are not described in this article, but a review can be found in the literature (Phillips and Wills 1987;Lester and Beck 1975). The dependent variable of interest is the suicide count for each day of the week following a suicide (or event).…”
Section: Time Series Analysismentioning
confidence: 99%